Philip P. answered • 03/19/14

Tutor

5.0
(472)
Effective and Patient Math Tutor

Hi Dalia:

A

_{n}= 2 + 5*(n-1), where n= 1, 2, 3, ...The first term occurs when n=1:

A

_{1}= 2 + 5(1-1) = 2The other terms work the same way, just plug in the different values of n (n = 2, 3, 4, 5).

The common difference is just the difference between one term and the next one after it. To compute it, do the following subtraction:

Common Difference = A

_{n+1}- A_{n}where

A

_{n+1}= 2 + 5((n+1) - 1) = 5n + 2A

_{n}= 2 + 5(n-1) = 2 + 5n - 5 = 5n - 3Subtract A

_{n}from A_{n+1}to get the answer. Let me know what you get in the comments and I'll let you if it's right.